Long‐term durability of a water‐contaminated quartz‐reinforced bismaleimide laminate. Issue 8 (10th November 2016) - Rodriguez, L.A.; García, C.; Grace, L.R.
Abstract : The long‐term structural viability of a six‐ply water‐contaminated quartz fiber‐reinforced bismaleimide laminate is investigated via dynamic mechanical analysis and flexural strength assessment over a four‐year experimental time frame. Water contamination is achieved via immersion in water at 25°C for short‐term (2 weeks and 1 month), long‐term (6 months), and very long‐term (4 years) duration. Long‐term moisture uptake exhibits distinctly non‐Fickian behavior. Maximum moisture content exceeds 1.5% by weight after four years of immersion. Laminates exhibit a remarkable resistance to degradation for all exposure durations. Flexural strength decreased by roughly 5% in the worst case. Further, no significant change in glass transition temperature was observed. Scanning electron microscopy revealed no micro‐crack formation and a relatively low incidence of fiber–matrix debond. Experimental evidence suggests that quartz fiber‐reinforced bismaleimide is a viable option for long‐term moisture‐prone structural applications at moderate temperatures. POLYM. COMPOS., 39:2643–2649, 2018. © 2016 Society of Plastics Engineers